Back Cover: SiIV Incorporation into a [28]Hexaphyrin That Triggered Formation of Möbius Aromatic Molecules (Chem. Eur. J. 27/2014). Issue 27 (1st July 2014) - Ishida, Shin‐ichiro; Tanaka, Takayuki; Lim, Jong Min; Kim, Dongho; Osuka, Atsuhiro
<x xml:space="preserve">Abstract</x> The first synthesis of [28]hexaphyrin–silicon complexes has been achieved. The coordination sphere of the encapsulated SiIV atom effectively twisted the skeletons of the complexes leading to features consistent with Möbius aromaticity. Selective desilylation of the [28]hexaphyrin–SiIV complex under Tamao–Fleming oxidation conditions gave the free base β‐monohydroxylated [28]hexaphyrin analogue, which also demonstrated distinct Möbius aromaticity. This is the first example of a Möbius aromatic [28]hexaphyrin conformationally rigidified by intramolecular hydrogen‐bonding interactions. For more information, see the Communication of D. Kim, A. Osuka et al. on page 8274 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>